Agropastoralism and sustainable development: the recognition of agropastoralism in the framework of international conventions - Rössler M. (Pastoralisme méditerranéen : patrimoine culturel et paysager et développement durable, 2010)
The presentation focuses on the integration of the agropastoralism in the operations of the 1972 World Heritage Convention, considering the combined works of man and nature in the Convention and since 1992 the inclusion of the cultural landscape categories into the Operational Guidelines. Furthermore, the paper presents a number of other international instruments and programmes including the Man and the Biosphere Programme (MAB) which also covers Biosphere Reserves in the Mediterranean Region including agropostoralist systems, such as the Arganeraie (Morocco), and the agro-ecosystems of the Oasis of the South of Morocco. The 2003 Convention for the Safeguarding of the Intangible Cultural Heritage also protects the living heritage related to agropastoral systems, but not the cultural and environmental values of the places as such, with the following elements as examples: Italy: Canto a Tenore, Sardinian Pastoral songs and Jordan: Cultural Space of the Bedu in Petra and Wadi Rum. The presentation then reviews sites included on the World Heritage List, such as the Laponian Area (Sweden) or Hortobagy (Hungary) as well as sites included in national Tentative Lists such as The Transhumance: The Royal Shepherd's Track (Italie), the nominated site of Les Cévennes et les Grandes Causses, France or the Mesta Livestock Trails (Spain). Finally the provisions of the Operational Guidelines concerning sustainable development, recommendations of previous expert meetings and Committee decisions are analyzed; as well as links to other programmes in the UN system (MAB, FAO-GHIAS) and beyond (IUCN) and the World Report on Cultural Diversity (UNESCO 2009).
2. Réunion Thématique d'Experts sur le Pastoralisme Méditerranéen, 2009/11/12-14, Tirana (Albanie)